2022
DOI: 10.1002/jsfa.11762
|View full text |Cite
|
Sign up to set email alerts
|

Investigating particle‐size‐induced changes in composition, physical, rheological, and bioactive properties of black tea powder

Abstract: BACKGROUND: People brew tea to drink an infusion that only contains 25% water-soluble constituents, leading to most of the insoluble materials being wasted. Tea powder could be drunk directly by mixing with water without producing any waste. Tea powder can also be used as a natural additive to improve the flavour and taste in beverages and foods. Much detailed information on the particle properties of tea powder is required with its increasing consumption. The aim of this study was to investigate the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The particle size distribution of the C. deserticola powders was analyzed using a LS13320 steam laser diffraction particle size analyzer (Beckman Coulter, Inc, USA). The span of particle size distribution was calculated with Equation (1) (Zhu et al, 2022): Span=D90D10D50 where D 90 , D 50 , and D 10 are the particle size of the equivalent volume at 90%, 50%, and 10% additive volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The particle size distribution of the C. deserticola powders was analyzed using a LS13320 steam laser diffraction particle size analyzer (Beckman Coulter, Inc, USA). The span of particle size distribution was calculated with Equation (1) (Zhu et al, 2022): Span=D90D10D50 where D 90 , D 50 , and D 10 are the particle size of the equivalent volume at 90%, 50%, and 10% additive volume.…”
Section: Methodsmentioning
confidence: 99%
“…Xi et al (2016) also found that Astragalus ultrafine powder could boost the immune response in chickens. Zhu et al (2022) reported that black tea ultrafine powder expressed a good bioactivity on reducing triglyceride and promoting high-density lipoprotein in rat model with hyperlipidemia. The wheat bran superfine powder had good dispersibility and solubility, so that it can be handily used in food (He et al, 2018).…”
mentioning
confidence: 99%
“…According to the Food and Agriculture Organization of the United Nations, the output of tea around the world was 7.02 million tons in 2020, of which China accounted for 42%. However, over 90% of tea was disposed of after the brewing process, leading to a significant increase in the production of tea waste. , It is noteworthy that tea waste is enriched with nitrogen functionalities (amino acids and caffeine) and has a much higher content of nitrogen (about 5%) than conventional biomass or coal (about 1%). , Therefore, unreasonable disposal of tea waste may probably lead to nitrogen pollution like harmful NO x emissions and water eutrophication. , Therefore, it is highly desirable to search for an effective method for the resource utilization of tea waste while alleviating the environmental load.…”
Section: Introductionmentioning
confidence: 99%
“…18 Tea is widely consumed as the most popular drink without alcohol because of its desirable flavors and various health benefits. 22 According to the Food and Agriculture Organization of the United Nations, the output of tea around the world was 7.02 million tons in 2020, of which China accounted for 42%. However, over 90% of tea was disposed of after the brewing process, leading to a significant increase in the production of tea waste.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation